2021
DOI: 10.1017/s1049023x21001345
|View full text |Cite
|
Sign up to set email alerts
|

“Motorcycle Ambulance” Policy to Promote Health and Sustainable Development in Large Cities

Abstract: Introduction: Motorcycles can be considered a new form of smart vehicle when taking into account their small and modern structure and due to the fact that nowadays, they are used in the new role of ambulance to rapidly reach emergency patients in large cities with traffic congestion. However, there is no study regarding the measuring of access time for motorcycle ambulances (motorlances) in large cities of Thailand. Study Objective: This study aims to compare access times to patients bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…124,125 Studies in India, 66 Zambia, 58 and Vietnam 57 showed only 7.5%, 5.9%, and 20.0% of emergency patients were transported by public or private ambulances. Also, ambulances were often lacking life-saving interventions 57,63,69 and BLS-trained personnel. 56,[66][67][68] Efficient time management is one of the key mechanisms to reducing mortality in emergency patients, especially for trauma and injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…124,125 Studies in India, 66 Zambia, 58 and Vietnam 57 showed only 7.5%, 5.9%, and 20.0% of emergency patients were transported by public or private ambulances. Also, ambulances were often lacking life-saving interventions 57,63,69 and BLS-trained personnel. 56,[66][67][68] Efficient time management is one of the key mechanisms to reducing mortality in emergency patients, especially for trauma and injuries.…”
Section: Discussionmentioning
confidence: 99%
“…59,81,82 Factors that affected response times included the distance from the hospital, location, type of emergency, and ambulance mechanism. Additionally, several studies found that response times in rural areas were generally longer than those in urban areas [83][84][85] (Table 3 38,39,59,61,63,69,74,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] ).…”
Section: Status Of Prehospital Emergency Care Servicesmentioning
confidence: 99%
“…In accordance with established protocol, these studies were independently reviewed by nonauthor members of the GEMLR editorial board and deemed appropriate to include. Apiratwarakul et al 67 . evaluated the utility of motor‐ambulance (“motorlance”) vehicles compared to ambulances in a congested city in Thailand by reviewing response time data and use of automated external defibrillator.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with established protocol, these studies were independently reviewed by nonauthor members of the GEMLR editorial board and deemed appropriate to include. Apiratwarakul et al 67…”
Section: Emdmentioning
confidence: 99%
“…As a result, the ED can prepare the necessary personnel and medical equipment to promptly initiate treatment upon the patient's arrival at the hospital. 5,6 However, the process of transferring information from an ambulance to the destination hospital takes a lot of time. During this period, the EMS members who are responsible for reporting the information must take their eyes off the patient assessment due to the radio base station on Thai ambulances that are designed to be mounted on the front of the vehicle so that the reporter cannot continuously see and assess the patient's condition.…”
Section: Introductionmentioning
confidence: 99%